Does DRD2 Taq1A Mediate Aripiprazole-Induced Gambling Disorder? A Pharmacogenetic Hypothesis - Miuli, Andrea; Pettorruso, Mauro; Romanelli, Ester; Stigliano, Gianfranco; Di Giuda, Daniela; De-Giorgio, Fabio; Martinotti, Giovanni; di Giannantonio, Massimo (Frontiers in Psychiatry, 2020)
Second generation antipsychotics (SGA) are a pharmacological class widely used in psychiatry thanks to their efficacy and good tolerability profile. One of the most used SGA is aripiprazole (ARI) because of its several formulations and safe metabolic and cardiac profile. As reported in a recent review, there are growing numbers of reports about ARI-induced gambling disorder (ARI-induced GD) which should encourage clinicians to use ARI more cautiously. Given the common genetic susceptibility of both GD and ARI’s clinical response to a genetic polymorphism on the D2 receptor (DRD2/ANKK1 Taq1A; rs1800497), the hypothesis regarding the origin of this phenomenon could be found in the altered sensitization of dopamine’s receptors that certain individuals carry genetically. The identification of a possible genetic susceptibility (detectable by genetic tests) could provide clinicians with an explanation for the ARI-induced GD and the possibility of using genetic screening tools for those cases of suspected predisposition; this would allow the clinician to prescribe ARI with less apprehension. The confirmation of this hypothesis through future pharmacogenetic studies may be useful for clinicians to have a correct understanding of the phenomenon.